Pilgrimage and Economy in the Ancient Mediterranean - Kristensen, Troels Myrup,; Collar, Anna, (Religions in the Graeco-Roman World ;, 2020)
In Pilgrimage and Economy in the Ancient Mediterranean , Anna Collar and Troels Myrup Kristensen bring together diverse scholarship to explore the socioeconomic dynamics of ancient Mediterranean pilgrimage from archaic Greece to Late Antiquity, the Greek mainland to Egypt and the Near East. This broad chronological and geographical canvas demonstrates how our modern concepts of religion and economy were entangled in the ancient world. By taking material culture as a starting point, the volume examines the ways that landscapes, architecture, and objects shaped the pilgrim's experiences, and the manifold ways in which economy, belief and ritual behaviour intertwined, specifically through the processes and practices that were part of ancient Mediterranean pilgrimage over the course of more than 1,500 years.